Investigation on the Degree of Reaction and Strength Performance of Fly Ash Based Geopolymer Binder with Alternnative Chemical Reagents - Kusbiantoro, Andri; Norbaizurah, Rahman (Trans Tech Publications, 2015)
The existence of high calcium contents in fly ash will contribute to the rapid stiffening and low workability of geopolymer paste. This study reports the feasibility of sodium nitrate and citric acid as the alternative admixtures for geopolymer binder. The effects of sodium nitrate and citric acid were independently evaluated at 0.5%, 1.5% and 2.5% of fly ash weight in geopolymer mixture. The effect of these admixtures on fresh geopolymer characteristic was evaluated through series of setting time and flow table workability tests, while degree of hydration, compressive strength and porosity tests were conducted to provide fundamental information on the hardened properties of geopolymer paste. Based on the result of degree of reaction, the inclusion of sodium nitrate in fly ash based geopolymer will increase the level of degree of hydration. Nevertheless, this result is in contrast with citric acid inclusion where degree of hydration decreased along with the increasing dosage of citric acid in the mixture. Strength development of geopolymer paste,particularly during the early age, appears to be affected by various geopolymerization rate presented by these admixtures.